Pemodelan Sistem Pakar Identifikasi Tingkat Stres Karyawan dengan Metode Certainty Factor - Handan Franata Simarmata; Agus Budiyantara (Pusat Riset dan Inovasi Nasional, 2024)
Expert systems work by collecting knowledge from experts in the form of rules or knowledge bases, then using an inference engine to analyze situations and produce decisions or suggestions. Apart from that, it is often used in the fields of medicine, engineering, finance, etc., related to this, especially the process of identifying the level of stress experienced by employees in the company so that they can find out more, therefore an expert system application design is needed for identification using the method. certainty factor, based on the certainty factor which has a concept based on symptoms and diagnoses from the weight of an expert's value and the user's value, calculated using the formula in CF, the final result is the creation of an expert system application for identifying employee stress levels based on a website.